Perancangan Website Manajemen Event sebagai Solusi Pengelolaan Kegiatan di Bagian Kesejahteraan Rakyat Kantor Bupati Deli Serdang - Nurul_Fikria, Nurul Fikria; Ragilia Putri Dinanti; Ahmad Taufik Al Afkari Siahaan (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
The Deli Serdang Regency Office's People's Welfare (Kesra) is a solution to administrative processes that are still carried out manually, such as participant registration, event data management, and information distribution, which often cause delays and data errors. This web-based system is designed to automate event management processes to make them faster, more accurate, and more transparent. The research methods included needs analysis, system design, implementation, and functional testing to ensure the system's suitability for the agency's needs. The results of the study show that the system is capable of providing key features such as participant registration, event management, attendance management, and real-time reporting. The implementation of the system has proven to increase work efficiency because activity data is more organized, easily accessible, and minimizes the potential for duplication and recording errors. The synthesis of the results indicates that this information system has successfully met the research objectives by supporting the digitization of work processes in the local government environment, particularly in the management of activities in the field of public welfare. In conclusion, this information system is capable of improving data accuracy, speeding up administrative processes, and facilitating activity coordination, although advanced features such as automatic notifications and digital document management still need to be developed to improve the quality of the system in the next phase.